LITERARY TEXT CONVERSION AS A FORM OF WRITING LITERACY ACTIVITIES - Triwidayati, Katarina Retno (Sanata Dharma University, 2019)
The survey of literacy rate held by the international institution has placed Indonesia in the last position compared to other countries surveyed. This shows how low the countryâ€™s reading and writing culture. On the other hand, the Indonesian language becomes the subject that is positioned as the medium to communicate diverse concepts of knowledge. Therefore, the Indonesian language is used as the instrument to gain knowledge or, to put it simply, topics discussed in Indonesian language learning involve other subjects. In addition, text-based learning is an important thing in the implementation of Indonesian language learning. One of the texts that can be used in learning Indonesian is literary texts. This article discusses the description of text-based language learning in forms of the text conversion and the example of text-based language learning using literature as the main text. Learning using literary text conversion is one of the writing literacy activities that can be implemented in schools.DOI:Â 10.24071/ijhs.2019.020209